Perceptions and trends in the use of community pharmacies in Ghana - Grace Adjei Okai; Gordon Abekah-Nkrumah; Patrick Opoku Asuming (Journal of Pharmaceutical Policy and Practice, 2019)
Objective To examine the patterns in utilization of community pharmacies and perceptions of the general public towards community pharmacists’ role in health services delivery. Method A cross-sectional household survey was conducted in Ga West district. A total of 497 adults (18 years and above) were chosen using a three-stage cluster random sampling technique. information on respondents’ contact with community pharmacies (i.e. 12 months prior to the study), reasons for visiting the pharmacies, factors influencing the choice of a particular pharmacy and perception towards community pharmacists’ roles were collected. Data collected were analyzed using stata version 14. Key findings Out of the 497 respondents, 415 indicated that they had used pharmacies within the last 12 months prior to the study, while 82 indicated that they had not used the facilities within the same time frame. majority of the pharmacy users (33.7%) visited community pharmacies once a month. Approximately 84% of the pharmacy users frequently visited community pharmacies to get treatment for minor ailments. most users (about 75%) chose to visit a particular pharmacy as it was close to their home/workplace/hospital/clinic. More than half of the pharmacy users identified the pharmacist as the first point of contact in case of any drug-related problem. Less than half of the respondents (44.9%) perceived community pharmacists as health professionals with a good balance between health and business matters. Conclusion The findings of the study suggest that beside the fact that majority of the respondents believe that community pharmacists are responsive, friendlier and have the capacity to handle minor ailments, they are indeed using community pharmacies for the treatment of minor ailments. It will therefore be important to develop appropriate policy and regulations that enables community pharmacies to adequately participate in the delivery of primary care and thereby improve population health.